Variability of Diagnostic Imaging in a Suicidal Attempt with Insulin - Eduardo, Pujol Freire Andres; Mariona, Badia Castello; Angelica, Morales Hernandez Dulce; Jorge, Rubio Ruiz; Angels, Furro Crusat; Beatriz, Garcia Ruiz; Jesus, Caballero Lopez (Archives of Clinical and Medical Case Reports, 2022)
We present a case report of an autolytic attempt with insulin in a nondiabetic patient which shows an initial Magnetic Resonance which usually indicates good prognosis, in contrast with the second one. After one week the control MRI drastically changes with the recovery of most white matter lesions but with multiple new ones in grey matter, darkening greatly this patient prognosis, therefore showing the variability of diagnostic imaging in this kind of cases.